Implications of Metropolitan Policy Mobility: Tracing the Relevance of Travelling Ideas for Metropolitan Regions. - Fricke, Carola (Springer, 2020)
This chapter traces the implications of policy mobility for metropolitan regions. It addresses the context and conditions of policy movements while reflecting on the consequences of mobile policy ideas from the perspective of metropolitan regions. To understand the impacts of metropolitan policy mobility, this chapter first asks who profits from the increased travelling of ideas. This is important because the winners of transnational policy mobility form an elite of metropolitan regions with the capacity, resources and interest to act beyond their national and regional boundaries. Second, the chapter suggests an explorative perspective on where policy mobility is leading the political development of metropolitan regions. Accordingly, the chapter moves away from a focus on transferred ideas and transfer mechanisms towards the reception and adaptation of travelling policies in the local context. Finally, the chapter sheds light on the relevance of policy mobility for everyday routines and formal procedures in metropolitan regions. This includes not only examining the implications for policymaking on metropolitan issues at other scales, but also the possibilities of policy failure.
Keywords: Metropolregion; Wissenstransfer; Forschungstransfer; Ideenwettbewerb; Übertragung; Auswirkung; Regional Governance; Regionalpolitik; Ideentransfer